Lesion characteristics of long application time ablation using unipolar half-normal saline irrigation and bipolar normal saline irrigation - Takumi Kasai; Osamu Saitoh; Ayaka Oikawa; Naomasa Suzuki; Yasuhiro Ikami; Yuki Hasegawa; Sou Otsuki; Takayuki Inomata; Hiroshi Furushima; Masaomi Chinushi (Indian Pacing and Electrophysiology Journal)
Introduction: Unipolar radiofrequency (RF) ablation using half-normal saline irrigation (UNIP-HNS) and bipolar RF ablation using normal saline irrigation (BIP-NS) are effective to treat arrhythmias from inside thick myocardium. However, differences between these two ablations when using a long application time had not fully been studied. Methods: UNIP-HNS, BIP-NS and unipolar RF ablation using normal saline irrigation (UNIP-NS) were applied for 120 s (30 W and 20-g contact) to porcine endocardial wall (≧15.0 mm thickness). Results: All ablations (30 applications each in UNIP-HNS and BIP-NS, and 20 applications in UNIP-NS) were successfully accomplished without steam-pop. Total impedance decline was largest in BIP-NS followed by UNIP-HNS and UNIP-NS. UNIP-HNS created larger surface lesions and greater maximum lesion width under the surface than those by UNIP-NS and BIP-NS. Endocardial lesion depth in UNIP-HNS and BIP-NS were deeper than that in UNIP-NS, but with no difference between UNIP-HNS and BIP-NS, when selecting non-transmural lesions. Similar results were obtained when all lesions (non-transmural and transmural) were included and endocardial lesion depth of the transmural lesions (13/30 applications of BIP-NS) was estimated as 50 % of the myocardial thickness. Lesion length in the transverse myocardial wall (endocardial plus epicardial lesions) was greatest in BIP-NS. Conclusions: Longer application time ablation (30 W) targeting the thick myocardium was performable in UNIP-HNS and BIP-NS. Since a transmural lesion and/or a deeper lesion into the myocardial wall are created, BIP-NS is preferable if two ablation catheters can be positioned on either side of the target.